Implementasi Filter Pre-Emphasis untuk Transmisi Sinyal Audio pada Sistem Komunikasi FBMC-OQAM - Anggun Fitrian Isnawati; Jans Hendry (Departemen Teknik Elektro dan Teknologi Informasi, Fakultas Teknik, Universitas Gadjah Mada, 2019)
High speed data transmision demands broader bandwidth. This has an effect towards the limitation of frequencies spectrum allocation as well as interference. To solve this, multi carrier modulation is one of choices. Having better power spectral density compared to OFDM, the FBMC-OQAM has been chosen as the multi carrier modulation. The FBMC is equipped with Poly Phase Network filter, makes it able to achieve better PSD. Frequently used filter, which is pre-emphasis, is popular in speech processing that is possibly able to be extended in use. Pre-emphasis is also accompanied with de-emphasis filter, which is similar to FBMC. Pre-emphasis filter suppresses low frequency magnitudes and emphasizes higher frequency. By assuming that noise presents in higher frequency, an approachment to protect audio signal by itself is proposed. Random noise is broadband signal where frequencies can have ranges from lower to higher with smaller magnitudes compared to signal. By providing slots in audio higher frequency and magnitudes, random noise occupied those slots with relatively weak magnitudes then sent through the air. At the receiver, a de-emphasis filter invert the process to restore signal by de-emphasizing higher frequency and removing noise as well. The result shows better BER with this approachment. For example, when Eb/No was 13 dB, BER with and without pre-emphasis are approximately 0.0184 dB and 0.0187 dB, consecutively. It means there was 250 bits or approximately 32 points has been corrected. It shows that pre-emphasis can work along with PPN FBMC filter to gain better BER values.